Responses of Phosphorus Use Efficiency, Grain Yield, and Quality to Phosphorus Application Amount of Weak-Gluten Wheat - Xin-kai ZHU; Chun-yan LI; Zong-qing JIANG; Lian-lian HUANG; Chao-nian FENG; Wen-shan GUO; Yong-xin PENG (Journal of Integrative Agriculture, 2012)
Phosphorus (P) is one of the most widely occurring nutrients for development and growth of wheat. In this study, the effects of P application amount on grain yield, protein content, and phosphorus use efficiency (PUE) were studied by agronomic management of P fertilizer on spring weak-gluten wheat (Triticum aestivum L.) grown under field conditions for 2 yr. The experiments were performed at five levels of P2O5 application amount, including 0, 72, 108, 144, and 180 kg ha−1. As a result, with increase in P fertilizer, grain yield, and P agricultural efficiency (AEP) increased in a quadratic equitation, but partial factor productivity of P (PFPP) decreased in a logarithmic eq. When 108 kg ha−1 P2O5 was applied, the grain yield reached the highest level, but the protein content in gain was lower than 11.5%, a threshold for the protein content to evaluate weak-gluten wheat suitable for production of cake and biscuit. Yangmai 13 and Ningmai 9 could tolerate to higher P level of soils than Yangmai 9 that had more loss in grain yield when P fertilizer was over-applied. AEP had a concomitant relationship with grain yield and was a better descriptor for P use efficiency in the wheat. A high P use efficiency resulted in leaf area index (LAI), increased chlorophyll content and photosynthetic rate, and stable acid phophatase (APase) activity to accumulate more dry matter after anthesis, which explained that the optimum P fertilizer increased grain yield and improved grain quality of weak-gluten wheat.